ANALISIS YURIDIS PERMASALAHAN-PERMASALAHAN HUKUM YANG BERKAITAN DENGAN NOTARIS DALAM PEMBUATAN AKTADI MAJELIS PENGAWAS WILAYAH NOTARIS (MPWN) SUMATERA UTARA - RASYADA ABDILLAH (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Dr. T. Keizerina Devi A, SH, CN, MHum2. Dr. Jelly Leviza, SH, MHum3. Notaris Dr. Henry Sinaga, SH, MKnIn exercising their authorities, Notaries are frequently reported by concerned parties concerning authentic deeds to the Regional Supervisory Council of Notaries of North Sumatera. The cases are caused by the authentic deeds produced by the notaries themselves. There are at least 4 (four) potential problems to make the notaries entangled with administrative sanctions ordered by the Regional Supervisory Council of Notaries of North Sumatera, namely: when the deed is being prepared by concerned parties, there is apparently another party who feels injured e.g. by a third party; notaries’ negligence/ carelessness in preparing authentic deeds; notaries’ intention in preparing authentic deeds to benefit only one party or that the notary is includeded as one of the concerned parties that results in turning the deeds into underhanded deeds; and that persons appearing provide false information/data in the preparation of authentic deeds.Keywords: Notary, the Regional Supervisory Council of Notaries of North Sumatera, Notarial Deed